Development and test of sets of 3D printed age-specific thyroid phantoms for 131I measurements. (16th May 2017) - Beaumont, Tiffany; Ideias, Pedro Caldeira; Rimlinger, Maeva; Broggio, David; Franck, Didier
Abstract: In the case of a nuclear reactor accident the release contains a high proportion of iodine-131 that can be inhaled or ingested by members of the public. Iodine-131 is naturally retained in the thyroid and increases the thyroid cancer risk. Since the radiation induced thyroid cancer risk is greater for children than for adults, the thyroid dose to children should be assessed as accurately as possible. For that purpose direct measurements should be carried out with age-specific calibration factors but, currently, there is no age-specific thyroid phantoms allowing a robust measurement protocol. A set of age-specific thyroid phantoms for 5, 10, 15 year old children and for the adult has been designed and 3D printed. A realistic thyroid shape has been selected and material properties taken into account to simulate the attenuation of biological tissues. The thyroid volumes follow ICRP recommendations and the phantoms also include the trachea and a spine model. Several versions, with or without spine, with our without trachea, with or without age-specific neck have been manufactured, in order to study the influence of these elements on calibration factors. The calibration factor obtained with the adult phantom and a reference phantom are in reasonable agreement. In vivo calibration experiments with germanium detectors have shown that the difference in counting efficiency, the inverse of the calibration factor, between the 5 year and adult phantoms is 25% for measurement at contact. It is also experimentally evidenced that the inverse of the calibration factor varies linearly with the thyroid volume. The influence of scattering elements like the neck or spine is not evidenced by experimental measurements.